Kindiling And Perception Of Qr-Images Using Raspberry-PI (International Journal of Engineering and Computer Science, 2015)
The QR Codes can be detected by webcam which is connected to ARM micro controller through USB device and the image is processed by using image processing technique. Image processing is any form of signal processing for which the input is an image, such as a photograph or video frame; the output of image processing may be either an image or a set of characteristics or parameters related to the image. In this project we are not only recognizing QR code but also generating color image from the QR code. The main advantage of this project is to recognize the QR Code from the webcam and generates color image. The controller will display the results on display unit as well as we can store the QR code and color image into pen drive.